2021
DOI: 10.1111/eea.13086
|View full text |Cite
|
Sign up to set email alerts
|

Multigenerational consequences of aphid size on offspring phenotype and reproduction

Abstract: In many organisms, phenotype and fitness are strongly influenced by both current environmental factors and maternal effects. The low genetic variation, high phenotypic plasticity, and telescoping generations seen in aphids permit us to investigate the relative importance and potential interaction of maternal and current environments on phenotype. Although past studies have identified an influence of maternal host plant on offspring phenotype and reproduction in aphids, few have demonstrated the potential for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 62 publications
1
3
0
Order By: Relevance
“…We also showed that a poor maternal environment always constrains the body size, survival, and fecundity of the next generation. This has been reported in previous studies ( Hayden et al, 2021 ; Zehnder et al, 2007 ). However, trans-generational effects on organismal development are related to resource abundance, as parents reared in a resource-limited environment produce offspring of lower quality due to reduced nutrient supply ( Baker et al, 2018 ; Herman and Sultan, 2016 ).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…We also showed that a poor maternal environment always constrains the body size, survival, and fecundity of the next generation. This has been reported in previous studies ( Hayden et al, 2021 ; Zehnder et al, 2007 ). However, trans-generational effects on organismal development are related to resource abundance, as parents reared in a resource-limited environment produce offspring of lower quality due to reduced nutrient supply ( Baker et al, 2018 ; Herman and Sultan, 2016 ).…”
Section: Discussionsupporting
confidence: 91%
“…Under adverse conditions such as starvation ( Scharf, 2016 ), adult Sitobium avenae (Fabricius) aphids showed reduced longevity and fecundity ( Xu et al, 2019 ). Herbivorous insects exhibit a high degree of phenotypic and transgenerational plasticity in their physiological and behavioral responses to changes in host plant quality, which in turn affects how they interact with the plant ( Ashra and Nair, 2022 ; Hayden et al, 2021 ). Important life history traits of aphids, such as body size, survival, developmental rate, and fecundity, are negatively affected by a poor quality of the host plant ( Dixon, 1987 ; Hayden et al, 2021 ; Ríos Martínez and Costamagna, 2018 ) or when the plant is damaged by other herbivores ( Denno et al, 2000 ; Takemoto et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations